Detrital chromian spinels from Upper Ordovician deposits in the Precordillera terrane, Argentina: A mafic crust input - Abre, Paulina (2009)
The study of heavy minerals from the Caradocian Pavón Formation (central Argentina) suggests that MORB and continental intraplate flood basalts were among the source rocks for the detrital record. The Pavón Formation was deposited on the disputed exotic Precordillera terrane. Provenance studies on this formation revealed sedimentary rocks characterized by an upper continental crustal component mixed with a mafic source, where the latter could not be described. The detrital chromian spinels provide more information about this component. The detrital spinels were chemically separated into two groups. Group 1 shows characteristics typical for host rocks related to MORB (Cr# values are between 0.4 and 0.6, Fe2+# range from 0.2 to 0.4, and they have low TiO2 and low Fe3+# contents). Conversely, Group 2 has Cr# of 0.7, Fe2+# ranging from 0.5 to 0.8, higher Fe3+# and TiO2 contents up to 4.7%, and they are related to continental flood basalts. The detrital spinels are chemically and texturally compared to those hosted in probable source rocks. Although the mafic source still remains unknown, the presence of detrital chromian spinels within the Pavón Formation implies the existence of an oceanic crustal component closely related to the Precordillera terrane. © 2009 Elsevier Ltd. All rights reserved.